Bronchiolar Adenoma/Pulmonary Ciliated Muconodular Papillary Tumor: Potential Pitfall on Frozen Sections. Issue 6 (14th December 2020) - Shirsat, Hemlata; Zhou, Fang; Chang, Jason C; Rekhtman, Natasha; Saqi, Anjali; Argyropoulos, Kimon; Azour, Lea; Simms, Anthony; Melamed, Jonathan; Hung, Yin P; Roden, Anja C; Mino-Kenudson, Mari; et al.
Abstract: Objectives: To describe the histologic features that are helpful in the diagnosis of the rare bronchiolar adenomas/ciliated muconodular papillary tumors (BAs/CMPTs) during intraoperative consultation. Methods: Multi-institutional retrospective review of frozen sections of 18 BAs/CMPTs. Results: In 14 of 18 cases, BA/CMPT was the primary reason for sublobar lung resection, and in 4 cases, BA/CMPT was an incidental finding intraoperatively for resections performed for carcinoma in other lobes. There were 11 proximal-type/classic BAs/CMPTs and 7 distal-type/nonclassic BAs/CMPTs. Only 3 (16.7%) of 18 were correctly diagnosed at the time of frozen section, all of which were proximal type/classic. The remainder were diagnosed as adenocarcinoma (n = 7); invasive mucinous adenocarcinoma (n = 1); non–small cell lung carcinoma (n = 1); cystic mucinous neoplasm, favor adenocarcinoma (either mucinous or colloid type) (n = 1); favor adenocarcinoma, cannot exclude CMPT (n = 1); atypical proliferation (n = 2); mucinous epithelial proliferation (n = 1); and mucous gland adenoma (n = 1). Conclusions: BA/CMPT can potentially be misdiagnosed as carcinoma during intraoperative consultation. On retrospective review of the frozen sections, the presence of the following may help to avoid misdiagnosis: a mixture of bland ciliated columnar cells, mucinous cells, and, most important, a basal cell layer, as well as a lack of necrosis, significant atypia, and mitoses.